Utilization of Sidoarjo Volcanic Mud as Heterogeneous Catalyst in Persulfate Oxidation Process - Khairunnisa Faza Nisrina; Sandyanto Adityosulindro; Lucky Caesar Direstiyani (Universitas Diponegoro, 2024)
Advanced Oxidation Processes (AOP), such as persulfate oxidation is a promising contaminant removal agent for treating wastewater. In this study, Sidoarjo volcanic mud (VM) was applied as heterogeneous catalyst to support the persulfate oxidation process for Congo Red (CR) dye removal. The Sidoarjo volcanic mud is known to have a high iron content, making it a potential catalyst in AOP. This study was conducted under conditions of pH 2, CR 50 mg/L, and catalyst dosage 0.5 g/L and effective reaction volume of 300 mL. This experiment was conducted by comparing three types of catalysts: unmodified volcanic mud (UVM), impregnated volcanic mud (Fe-IVM), and calcined volcanic mud (CVM). The methods were carried out by comparing two methods, namely simultaneous and sequential. The obtained CR removal values for UVM, Fe-IVM, and CVM catalysts were 83.73%, 78.86%, 51.96% for simultaneous and 84.75%, 81.72%, and 87.69% for sequential method. Whereas the UVM catalyst has the highest CR removal value with a lower adsorption value of 16.89%. The production of sulfate radical analyzed by comparing the oxidation process of homogeneous and heterogeneous catalysts. It was shown that the application of VM catalyst as heterogeneous catalyst is very promising for dye removal in wastewater treatment.